INHIBITORY EFFECT OF BASE GEDE ETHANOL EXTRACT AGAINTS BACTERIAL GROWTH OF Escherichia coli - Wibisana, I Dewa Nyoman Adi Ningrat; Hendrayana, Made Agus; Sukrama, I Dewa Made; Budayanti, Ni Nyoman Sri (E-Jurnal Medika Udayana; Vol 13 No 9 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i09.P01, 2024)
Foodborne disease is a condition in which food is contaminated by microorganisms or chemicals, causing disease. One of the microorganisms that most often causes this condition is Escherichia coli. There is an assumption which states that, base gede/base genep has antibacterial properties which inhibit the growth of bacteria in typical Balinese food such as lawar. Various studies have proven that the basic ingredients of base gede have antibacterial activity obtained from secondary metabolites. The purpose of this study was to determine the phytochemical compounds contained in the base gede and the inhibitory power of the base gede in inhibiting the growth of the Escherichia coli ATCC 25922. This study examined the content of secondary metabolites qualitatively and the experimental test was the true experimental posttest only control group design. The method used was the disk diffusion (Kirby Bauer) with variations in the concentration of ethanol extract base gede as many as four groups (25%, 50%, 75% and 100%) and the negative control group was 96% ethanol and the positive control group ciprofloxacin 5g. The results of the phytochemical test found that the base gede ethanol extract contained phenols, saponins, tannins, alkaloids, terpenoids, and flavonoids. Inhibition test results observed inhibition zones formed at concentrations of 50%, 75%, 100% and K+ with diameters respectively 5.65+/-0.65 mm ; 7.00+/-1.35mm ; 7.78+/-1.18 mm dan 34.52+/-1.49 mm. Kruskal wallis test showed a value of p = 0.001 (p <0.05) which showed that the concentration group had an effect on the inhibition of E.coli ATCC 25922. There was a significant difference between the 50% and 100% concentrations obtained from the Mann-Whitney analysis with value of p = 0.043 (p<0.05). Keywords : Inhibition test, base gede, Escherichia coli